Long-lasting complete response status of advanced stage IV gall bladder cancer and colon cancer after combined treatment including autologous formalin-fixed tumor vaccine: two case reports - Imaoka, Yuki (World J Surg Oncol, 2017)
BACKGROUND: The prognosis of advanced (stage IV) cancer of the digestive organs is very poor. We have previously reported a case of advanced breast cancer with bone metastasis that was successfully treated with combined treatments including autologous formalin-fixed tumor vaccine (AFTV). Herein, we report the success of this approach in advanced stage IV (heavily metastasized) cases of gall bladder cancer and colon cancer. CASE PRESENTATION: Case 1: A 61-year-old woman with stage IV gall bladder cancer (liver metastasis and lymph node metastasis) underwent surgery in May 2011, including partial resection of the liver. She was treated with AFTV as the first-line adjuvant therapy, followed by conventional chemotherapy. This patient is still alive without any recurrence, as confirmed with computed tomography, for more than 5 years. Case 2: A 64-year-old man with stage IV colon cancer (multiple para-aortic lymph node metastases and direct abdominal wall invasion) underwent non-curative surgery in May 2006. Following conventional chemotherapy, two courses of AFTV and radiation therapy were administered sequentially. This patient has had no recurrence for more than 5 years. CONCLUSION: We report the success of combination therapy including AFTV in cases of liver-metastasized gall bladder cancer and abdominal wall-metastasized colon cancer. Both patients experienced long-lasting, complete remission. Therefore, combination therapies including AFTV should be considered in patients with advanced cancer of the digestive organs.